2021
DOI: 10.3390/diagnostics11020253
|View full text |Cite
|
Sign up to set email alerts
|

Increased Tenascin C, Osteopontin and HSP90 Levels in Plasmatic Small Extracellular Vesicles of Pediatric ALK-Positive Anaplastic Large Cell Lymphoma: New Prognostic Biomarkers?

Abstract: Over the past 15 years, several biological and pathological characteristics proved their significance in pediatric anaplastic lymphoma kinase (ALK)-positive anaplastic large-cell lymphoma (ALCL) prognostic stratification. However, the identification of new non-invasive disease biomarkers, relying on the most important disease mechanisms, is still necessary. In recent years, plasmatic circulating small extracellular vesicles (S-EVs) gathered great importance both as stable biomarker carriers and active players … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 40 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…12 Recently, SEV-derived SAA levels have also been found to be increased in pediatric patients with anaplastic lymphoma kinase (ALK)-positive anaplastic large-cell lymphoma (ALCL) relative to healthy controls. 13 Therefore, increased SAA levels in SEVs may also re ect the increased disease burden of malignant PCs and/or an in ammatory state within the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…12 Recently, SEV-derived SAA levels have also been found to be increased in pediatric patients with anaplastic lymphoma kinase (ALK)-positive anaplastic large-cell lymphoma (ALCL) relative to healthy controls. 13 Therefore, increased SAA levels in SEVs may also re ect the increased disease burden of malignant PCs and/or an in ammatory state within the bone marrow.…”
Section: Discussionmentioning
confidence: 99%
“…Lovisa et al [97] performed a proteomics study to compare plasma EV derived from pediatric ALCL patients and healthy donors and identified up to 50 proteins that were significant in EVs derived from ALCL patients [97]. Functional enrichment analysis revealed that these proteins are related to cell adhesion, glycosaminoglycan metabolic process, extracellular matrix organization, collagen fibril organization, and acute phase response, as well as the PI3K/AKT pathway [97].…”
Section: Pediatric Lymphomamentioning
confidence: 99%
“…Functional enrichment analysis revealed that these proteins are related to cell adhesion, glycosaminoglycan metabolic process, extracellular matrix organization, collagen fibril organization, and acute phase response, as well as the PI3K/AKT pathway [97]. This study suggested that these ALCL-derived EV proteins can be used as diagnostic and possibly prognostic parameters during diagnosis and ALCL disease monitoring [97]. Another proteomic study identified 11 unique proteins, including five upregulated in non-relapsed HL (e.g., isoform 2 preproprotein of complement C4-A, complement C4-B, fibrinogen Îł chain, inter-α-trypsin inhibitor heavy chain H2, and immunoglobulin heavy chain constant region mu) and six upregulated in relapsed HL (e.g., apolipoprotein A-I, apolipoprotein A-IV, clusterin, haptoglobin, α-1-acid glycoprotein 1, and transthyretin) [98].…”
Section: Pediatric Lymphomamentioning
confidence: 99%
“…A parallel proteomic analysis led to the identification of proteins involved in PI3K signaling that are enriched in exosomes from ALCL patients. The authors proposed three proteins, namely tenascin C, osteopontin and heat shock protein 90 as potential biomarkers for ALCL prognostic stratification [74]. Altogether, these studies open the possibility to assess the risk of relapse and to monitor the response to therapy in a disease where tissue re-biopsies are often difficult to obtain.…”
Section: Anaplastic Large-cell Lymphoma (Alcl)mentioning
confidence: 99%